Artistic choices of classical music lovers as a criterion of their level of tolerance towards other cultures and nations - Sasin, Magdalena (Granice tolerancji w sztuce i w wychowaniu, 2020)
This article presents the analysis of music lovers’ artistic choices in the context of their view on other national and cultural groups. Since music is a kind of nonverbal communication, the attitude to certain musical compositions might be perceived as an expression of the level of tolerance. Tolerance is interpreted here – according to Ija Lazari-Pawłowska – as a positive value, active attitude of understanding and respect. Traditional classical music lovers, who prefer music from centuries between 17th and mid 20th, are relatively conservative, while contemporary music lovers tend to be more open. Regardless of this fact, some musical compositions are characterized by the predominance of non- -musical content, which is a result of their background and way of presentation more than the intension of composers themselves. This situation indicates that many listeners are schematic in their perception. It reveals space for aesthetic education. However, this schematic attitude is often strengthened in school education; the opportunity to shape tolerance by using music must be assessed as an unfulfilled potential.